Factors that lead to ethical behavior among police at IPD Kuala Muda, Kedah / Nur Azila Ahmad and Wan Nor Shahirah Wan Hashim - Ahmad, Nur Azila; Wan Hashim, Wan Nor Shahirah (2018)
The purpose of the study is to identify the factor that leads to the ethical behavior among police at IPD Kuala Muda, Kedah. According to the report that was issued by Bureau Public Complaints (PCB) and Enforcement Agency Integrity Commission (EAIC) on 2014 shown Royal Malaysian Police (RMP) obtaining a high number of complaints which is more than 50% regarding the misconduct and abuse of power. The researchers are decided to use cross sectional design by using quantitative method. This method used as the data collection were collected at a particular time to answer all the research objective. This study is conducted by using the stratified sampling technique which are focusing on nine (9) departments at IPD Kuala Muda. The number of respondents is 265 for the data collection by using the sample size on formula table proposed by Uma Sekaran (2003). The methodologies used are descriptive analysis, correlation coefficient and multiple regressions for the test analysis. Based on the result from the analysis shows that there are significant relationship of dependent variable which is ethical behavior among police and independent variables namely organizational culture, leadership and personality traits. The result also shows that the most dominant factor that lead to ethical behavior among police at IPP Kuala Muda is organizational culture.